Math, asked by gsubrata2229, 1 year ago

Factorize:
x(x³–y³)+3xy-(x–y)

Answers

Answered by Anonymous
8

Answer:

x(x^3 - y^3) + 3xy - (x - y)

=> x((x - y)(x^2 + y^2 + xy) + 3xy - (x - y)

=> (x - y)(x^3 + xy^2 + x^y - 1) + 3xy

_________________

Answered by nikitasingh79
1

Given : x(x³ – y³) + 3xy(x – y)

= x(x – y) (x²  + xy + y²) + 3xy(x – y)

[By using the identity (a³ - b³) = (a - b) (a² + ab + b²)]

Here x(x – y) is a common factor :  

= x(x – y) [(x²+ xy + y² + 3y)]

= x(x – y) (x² + + y² xy  + 3y)

Hence, the factorisation of  x(x³ – y³) + 3xy (x – y) is  x(x – y) (x² + + y² xy  + 3y).

HOPE THIS ANSWER WILL HELP YOU…..

 

Similar questions :

Factorize:

a²x²+(ax²+1)x+a

 

Factorize:

x³-2x²y+3xy²-6y³

https://brainly.in/question/15898055

Similar questions